2020
DOI: 10.3390/w12020524
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Fungal Strains from Municipal Wastewater for the Removal of Pharmaceutical Substances

Abstract: Fungi have been shown to be promising candidates to be used in removal of pharmaceutical compounds during wastewater treatment processes. However, fungal growth, including removal efficiency, can be affected by several factors, such as temperature and the pH. The ability of fungal isolates to grow in the presence of carbamazepine, diclofenac, ibuprofen, and sulfamethoxazole was tested. Removal efficiency results indicated that a fungal isolate of Aspergillus luchuensis can completely (>99.9%) remove diclofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Several studies have demonstrated the participation of oxidase enzymes in the biodegradation/biotransformation of BPA, in particular fungi that produce laccases [ 77 , 78 ]. Daâssi et al [ 79 ] reported the efficiency of laccase from Coriolopsis gallica , Bjerkandera adusta, and T. versicolor in the biodegradation of BPA; C. gallica had the highest BPA removal rate (91%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the participation of oxidase enzymes in the biodegradation/biotransformation of BPA, in particular fungi that produce laccases [ 77 , 78 ]. Daâssi et al [ 79 ] reported the efficiency of laccase from Coriolopsis gallica , Bjerkandera adusta, and T. versicolor in the biodegradation of BPA; C. gallica had the highest BPA removal rate (91%).…”
Section: Resultsmentioning
confidence: 99%
“…374BPA. However, we cannot discard the participation or contribution of the xenobiotic de-375 toxification systems in this process as we stated for DFC degradation.376Several studies have demonstrated the participation of oxidase enzymes in the bio-377 degradation/biotransformation of BPA, in particular fungi that produce laccases[77,78].378 Daâssi et al [79] reported the efficiency of laccase from Coriolopsis gallica, Bjerkandera adu-379 sta, and T. versicolor in the biodegradation of BPA; C. gallica had the highest BPA removal…”
mentioning
confidence: 90%
“…This focuses attention on water treatment processes and raises questions on the lack of regulation for this biological pollutant. Although research has found that fungi can be useful in removing pharmaceutical compounds owing to their enzymatic processes, which can increase yields and enhance life cycles [34,35], this is not reason enough to tolerate their unconditional presence. The public health problem that they potentially represent, coupled with the fact that there is currently no regulation at a global level in the area of water treatment [34], and the scarcity in pathogenicity studies attributed to these organisms are causes of concern.…”
Section: Fungimentioning
confidence: 99%
“…Among these organic contaminants, involved in chemical pollution phenomena are antibiotics, analgesics, antiinflammatories, contrast agents or antiepileptics and pyretics. The latter are introduced into the environment through anthropogenic activities: industrial discharges, animal manure, wastewater from various treatments, waste and unused drugs caused by runoff from landfills household waste or waste water [3][4][5]. Recent studies claim that hospital wastewater is the pharmaceuticals main source in the aquatic environment [3,6,7].…”
Section: Introductionmentioning
confidence: 99%